"Stepping in the Gap to Make Family": Care Calculation and Grandparent Caregiving in Detroit, Michigan. Issue 1 (10th March 2021) - Richards, Fayana
Abstract: Scholars have long recognized the role that older Black American women play in providing care for their own grandchildren, nieces, nephews, and even non‐kin, arguing that kinship and caregiving relationships have been shaped by historical and structural factors. In this article, I consider intensive grandchild caregiving among Black American grandparents, primarily grandmothers, living in Detroit, Michigan. I highlight how the decision and process of providing care involves a "care calculation" where grandmothers evaluate their decision to caregive against existing financial, emotional, and bodily resources. In doing so, I argue that grandparent caregiving should be understood as a responsive and intentional process, where the decision to care for grandchildren and the performance of care work is more than simply responding to a set of certain circumstances and/or obligations based on biological kinship relations.